Comprehensive two-dimensional gas chromatography combined to multivariate data analysis for detection of disease-resistant clones of Eucalyptus - Hantao, Leandro Wang; Toledo, Bruna Regina; Lima Ribeiro, Fabiana Alves de; Pizetta, Marilia [UNESP]; Pierozzi, Caroline Geraldi [UNESP]; Furtado, Edson Luiz [UNESP]; Augusto, Fabio (Elsevier B.V., 2013)
In this paper it is reported the use of the chromatographic profiles from volatile fractions of plant clones - in this case, hybrids of Eucalyptus grandis x Eucalyptus urophylla - to determine specimens susceptible to rust disease. The analytes were isolated by headspace solid phase microextraction (HS-SPME) and analyzed by comprehensive two-dimensional gas chromatography combined to fast quadrupole mass spectrometry (GC x GC-qMS). Parallel Factor Analysis (PARAFAC) was employed for estimate the correlation between the chromatographic profiles and resistance against Eucalyptus rust, after preliminary variable selection performed by Fisher ratio analysis. The proposed method allowed the differentiation between susceptible and non-susceptible clones and determination of three resistance biomarkers. This approach can be a valuable alternative for the otherwise time-consuming and laborintensive methods commonly used. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Comprehensive two-dimensional gas; chromatography; Mass spectrometry; Metabolic profile; Parallel factor analysis; Puccinia psidii; Resistance biomarkers